Modulação do sistema renina-angiotensina aldosterona intracelular de células mesangiais humanas submetidas ao estímulo da aldosterona - Stoll, Danielle [UNIFESP] (2017)
An important target of the renin angiotensin aldosterone system (RAAS) is the kidney, responsible for controlling the electrolyte balance. Currently, several studies have demonstrated the existence of a local RAAS in different tissues, including the renal, being distributed throughout the nephron. Aldosterone is a mineralocorticoid that plays a critical role in classical RAAS, whose description in mesangial cells (MC) still needs to be elucidated. MCs are essential for maintaining glomerular integrity and play a role in modulating glomerular filtration. The study of the role of aldosterone in modulating local RAAS in mesangial cells is important in understanding the physiological mechanisms and in particular the variations triggered in the angiotensin converting enzyme (ACE) / angiotensin II (ANGII) / angiotensin receptor type 1 (AT-1) and angiotensin-converting enzyme 2 (ACE2) / angiotensin- (1-7) [ANG- (1-7)] / MAS Receptor axes. Based on the data above, our aim was to investigate whether the aldosterone stimulus can modulate the intracellular RAAS of immortalized human mesangial cells (IHMC) by evaluating both axes ACE/ANGII/AT-1 and ACE2/ANG-(1-7)/Mas. For this, the cell viability, protein expression and enzymatic activity were evaluated under physiological, supra and sub physiological doses of aldosterone and in the presence of the mineralocorticoid receptor antagonist (MR), spironolactone (SPI). Our results showed that physiological doses of aldosterone improve the viability of IHMC by approximately 20% in relation to the control, spironolactone and 10 nM stimulated groups. High doses of aldosterone increased ACE expression and activity respectively, and the 10 nM stimulus was able to increase the activity of this enzyme by up to 3 times in relation to the physiological dose of 0.1 nM. The effect of aldosterone on the catalytic activity of ACE was completely abolished with the pre-treatment of SPI. Elevated doses of aldosterone increased the expression of ACE 2 and MAS receptor, but did not alter the catalytic activity of the enzyme allowing the production of ANG-(1-7) and altering the internalization profile of this peptide in these cells. Spironolactone on binding to its receptor triggering an antagonistic effect was able to modulate the localization of ANG II, AT-1 and MAS receptor whose expression was also decreased. Our data suggest that both aldosterone and the MR receptor antagonist can modulate both axes.